Plasmodium falciparum artemisinin resistance monitoring in Sabah, Malaysia : in vivo therapeutic efficacy and kelch13 molecular marker surveillance - Grigg, Matthew J. (2019)
Background:Spreading Plasmodium falciparum artemisinin drug resistance threatens global malaria public health gains. Limited data exist to define the extent of P. falciparum artemisinin resistance southeast of the Greater Mekong region in Malaysia. Methods:A clinical efficacy study of oral artesunate (total target dose 12 mg/kg) daily for 3 days was conducted in patients with uncomplicated falciparum malaria and a parasite count < 100,000/µL admitted to 3 adjacent district hospitals in Sabah, East Malaysia. On day 3 and 4 all patients were administered split dose mefloquine (total dose 25 mg/kg) and followed for 28 days. Twenty-one kelch13 polymorphisms associated with P. falciparum artemisinin resistance were also evaluated in P. falciparum isolates collected from patients presenting to health facilities predominantly within the tertiary referral area of western Sabah between 2012 and 2016. Results:In total, 49 patients were enrolled and treated with oral artesunate. 90% (44/49) of patients had cleared their parasitaemia by 48 h and 100% (49/49) within 72 h. The geometric mean parasite count at presentation was 9463/µL (95% CI 6757–13,254), with a median time to 50% parasite clearance of 4.3 h (IQR 2.0–8.4). There were 3/45 (7%) patients with a parasite clearance slope half-life of ≥ 5 h. All 278 P. falciparum isolates evaluated were wild-type for kelch13 markers. Conclusion:There is no suspected or confirmed evidence of endemic artemisinin-resistant P. falciparum in this pre-elimination setting in Sabah, Malaysia. Current guidelines recommending first-line treatment with ACT remain appropriate for uncomplicated malaria in Sabah, Malaysia. Ongoing surveillance is needed southeast of the Greater Mekong sub-region.